2006
DOI: 10.1111/j.1462-2920.2006.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cultivation‐dependent and molecular methods for studying the diversity of anoxygenic purple phototrophs in sediments of an eutrophic brackish lagoon

Abstract: Phototrophic anoxygenic purple bacteria play a key role in many aquatic ecosystems by oxidizing sulfur compounds and low-molecular-weight organic compounds using light as energy source. In this study, molecular methods based upon pufM gene (photosynthetic unit forming gene) were compared with culture-dependent methods to investigate anoxygenic purple phototrophic communities in sediments of an eutrophic brackish lagoon. Thirteen strains, belonging to eight different genera of purple phototrophic bacteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
2
21
0
1
Order By: Relevance
“…The pufM gene was amplified using the primers puf557F and puf750R (Karr et al 2003;Ranchou-Peyruse et al 2006). PCR amplification mixtures contain 5 ll of 109 PCR buffer without MgCl 2 , 3 ll of 25 mM MgCl 2 , 1 ll of each deoxynucleoside triphosphate at 10 mM, 0.5 ll of each forward and reverse primer at 125 lg/ml, 1 ll of DNA template (ca.…”
Section: Nucleic Acid Extraction and Pcr Amplificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The pufM gene was amplified using the primers puf557F and puf750R (Karr et al 2003;Ranchou-Peyruse et al 2006). PCR amplification mixtures contain 5 ll of 109 PCR buffer without MgCl 2 , 3 ll of 25 mM MgCl 2 , 1 ll of each deoxynucleoside triphosphate at 10 mM, 0.5 ll of each forward and reverse primer at 125 lg/ml, 1 ll of DNA template (ca.…”
Section: Nucleic Acid Extraction and Pcr Amplificationmentioning
confidence: 99%
“…Their higher growth rates and efficiency in organic carbon utilization over strict heterotrophs are likely to make them dynamic and significant contributors to the organic carbon production and cycling within the stabilization ponds (Gasol et al 2008) and it has been shown that these bacteria play a key role in a diverse range of oxic ecosystems (Buchan et al 2005;Oz et al 2005). Among the aerobic anoxygenic phototrophic bacterial group, some representatives may be able to grow under anaerobic conditions (Ranchou-Peyruse et al 2006).…”
Section: Aerobic Anoxygenic Phototrophic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…L, M and H polypeptides function to bind bacteriochlorophyll and carotenoids such as spirilloxanthin, lycopenal and rhodopinal as well as quinones. The pufM gene has been widely used to investigate Photosynthetic Anoxygenic Purple Bacteria (PAPB) diversity in natural environments (Schwalbach and Fuhrman 2005;Yutin et al, 2005;Okubo et al, 2006, Ranchou-Peyruse et al, 2006. PAPB grow correctly in natural and polluted environments by forming colored microbial mats and by developing massive growth (blooms) (Okubo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular analyses based on the pufM gene encoding the M-subunit of the photosynthetic reaction center have explored AAP bacterial diversity using the polymerase chain reaction (PCR) (Béjà et al, 2002;Yutin et al, 2005;, denaturing/temperature gradient gel electrophoresis (DGGE/TGGE) (Yutin et al, 2008;Lehours et al, 2010), terminal restriction fragment length polymorphism (T-RFLP) (Ranchou-Peyruse et al, 2006) and metagenomic analysis (Yutin et al, 2007). Although these DNA-based approaches have given insight into the diversity of AAP bacteria, analysis of relevant functional communities is still a challenge, as DNA could be stable in resting cells and even dead cells and may also be present as extracellular DNA.…”
Section: Introductionmentioning
confidence: 99%